2020
DOI: 10.1083/jcb.202004202
|View full text |Cite
|
Sign up to set email alerts
|

The mitotic protein NuMA plays a spindle-independent role in nuclear formation and mechanics

Abstract: Eukaryotic cells typically form a single, round nucleus after mitosis, and failures to do so can compromise genomic integrity. How mammalian cells form such a nucleus remains incompletely understood. NuMA is a spindle protein whose disruption results in nuclear fragmentation. What role NuMA plays in nuclear integrity, and whether its perceived role stems from its spindle function, are unclear. Here, we use live imaging to demonstrate that NuMA plays a spindle-independent role in forming a single, round nucleus… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 79 publications
1
6
0
Order By: Relevance
“…To determine whether these nuclear morphology defects depended on the ability of KIF22 to generate forces within the mitotic spindle, cells were treated with nocodazole to depolymerize microtubules and reversine to silence the spindle assembly checkpoint, allowing cells to enter and exit mitosis without assembling a spindle or segregating chromosomes ( Samwer et al, 2017 ; Serra-Marques et al, 2020 ; Figure 6D ). The solidity of nuclei was measured before chromosomes condensed ( Figure 6E ) and after mitotic exit ( Figure 6F ).…”
Section: Resultsmentioning
confidence: 99%
“…To determine whether these nuclear morphology defects depended on the ability of KIF22 to generate forces within the mitotic spindle, cells were treated with nocodazole to depolymerize microtubules and reversine to silence the spindle assembly checkpoint, allowing cells to enter and exit mitosis without assembling a spindle or segregating chromosomes ( Samwer et al, 2017 ; Serra-Marques et al, 2020 ; Figure 6D ). The solidity of nuclei was measured before chromosomes condensed ( Figure 6E ) and after mitotic exit ( Figure 6F ).…”
Section: Resultsmentioning
confidence: 99%
“…The NuMA-53BP1 interaction was reported to be located in the nucleoplasm when there is no DSB repair ( 23 ). The fact that IGF1R-NuMA colocalization was not inducible by IR in the present study suggested that the interaction most likely does not occur at the chromatin surrounding the DSB site, despite the structural and chromosome-binding roles of NuMA ( 48 ), as well as the transcription regulatory function of nIGF1R through DNA binding ( 14 ). The mechanism behind IGF1R-NuMA-53BP1 interactions could be either that IGF1R-NuMA and NuMA-53BP1 interactions are mutually exclusive or that they form a tripartite complex.…”
Section: Discussionmentioning
confidence: 50%
“…18 Multiple studies reported that NuMA dysfunction causes spindle pole-focusing defects, 16,[19][20][21][22][23] lagging chromosomes in anaphase, 24,25 and micronuclei formation in somatic cells. [26][27][28] Although these studies have linked NuMA depletion to chromosomal mis-segregation in mitosis, it has remained difficult to unequivocally attribute micronuclei formation to specific defects during metaphase, especially in terms of SAC satisfaction. In this study, we analyzed dynamic behaviors of chromosomes, kinetochores, checkpoint proteins, microtubules, and centrosomes in HCT116 colon cancer cells after rapidly depleting NuMA by the auxin-inducible degron (AID) system.…”
Section: Resultsmentioning
confidence: 99%